TELEVISION: LEISURE, CULTURE AND IDEOLOGY - Machado dos Santos, Adelcio; Antonio Córdova Ransolin , Marco; Tenconi , Daniel; Marton, Roberto; Sprandel da Silva, Solange (Revista Gênero e Interdisciplinaridade, 2026)
This article discusses the relevance of music as a central element of human culture, exploring its role in the construction of identities, the transmission of values and the promotion of social change. Music is analyzed in its multiple dimensions: as a cultural expression, an agent of social change and a product of the cultural industry. The impact of globalization and digitalization on access to and production of music is also addressed, highlighting both the benefits and the challenges of these processes, such as cultural homogenization and the commodification of artistic expressions. Independent and alternative music is presented as a force of resistance and diversity, capable of preserving traditions and fostering innovation. Finally, the article reinforces the importance of valuing musical diversity as a way of enriching culture and building more inclusive and connected societies.